Odpowiedź :
Zadanie 2.
a) [tex]5x*7=35x[/tex]
b) [tex]\left(-\frac{3}{4}x\right):\frac{4}{3}=\left(-\frac{3}{4}x\right)*\frac{3}{4}=-\frac{9}{16}x[/tex]
c) [tex]8(3a-5)=24a-40[/tex]
d) [tex]-2(-5a+4b-1)=10a-8b+2[/tex]
e) [tex]6y*8=48y[/tex]
f) [tex]\left(-\frac{4}{5}y\right):\frac{5}{4}=\left(-\frac{4}{5}y\right)*\frac{4}{5}=-\frac{16}{25}y[/tex]
g) [tex]7(4a-5)=28a-35[/tex]
h) [tex]-3(-6a+7b-1)=18a-21b+3[/tex]
Zadanie 3.
a)
[tex]-2t+5+8t+3-7t+13=-t+21\\t=-1\\-t+21=-(-1)+21=1+21=22[/tex]
b)
[tex]2\frac{1}{2}x-9y+4x+3y-\frac{1}{2}x=6x-6y\\x=-2\ ,\ y= \frac{1}{3}\\6x-6y=6*(-2)-6*\frac{1}{3}=-12-2=-14[/tex]
c)
[tex]-7t+3+9t-1-3t+17=-t+19\\t=-1\\-t+19=-(-1)+19=1+19=20[/tex]
Odpowiedź:
2.
a)
5x * 7 = 35x
b)
(-3/4x) * 4/3 = -x
c)
8(3a - 5) = 24a - 40
d)
-2(-5a + 4b - 1) = 10a - 8b + 2
e)
6y * 8 = 48y
f)
(-4/5y) : 5/4 = (-4/5y) * 4/5 = -16/25y
g)
7(4a - 5) = 28a - 35
h)
-3(-6a + 7b - 1) = 18a - 21b + 3
3.
a)
-2t + 5 + 8t + 3 - 7t + 13 = -t + 21 = 1 + 21 = 22
dla t = -1
b)
2 1/2x - 9y + 4x + 3y - 1/2x = 6x - 6y = 6(-2) - 6 * 1/3 = -12 - 2 = -14
dla x = -2; y = 1/3
c)
-7t + 3 + 9t - 1 - 3t + 17 = -t + 19 = 1 + 19 = 20
dla t = -1
Szczegółowe wyjaśnienie: